Prevalence and perceived importance of racial matching in the psychotherapeutic dyad: a national survey of addictions treatment clinical practices - Jesse A. Steinfeldt; Shondra L. Clay; Paul E. Priester (Substance Abuse Treatment, Prevention, and Policy, 2020)
Abstract Background Despite conflicting results in the literature concerning its efficacy in practice, racial matching has been identified as a component of culturally sensitive treatment. Methods This study examined the perceived importance and prevalence of racial matching by surveying a national sample of substance use disorder (SUD) centers from the Substance Abuse and Mental Health Services Administration (SAMHSA). Results Using univariate statistical analysis, results for the prevalence of racial matching revealed that in 58% of the clinics, there was the potential to match a counselor with a racially similar client, while in 39% of the clinics, there was no potential to provide such a match. Among the agencies that displayed a potential for racial matching, 26% of the respondents indicated that they never racially matched clients and therapists, 71% reported that they sometimes practice racial matching, 15% indicated that they usually racially match, and only 7% purported to always racially match clients and therapists. Results for the perceived importance of racial matching revealed that in both situations where treatment centers had the potential for racial matching and did not have the potential for racial matching, supervisors reported that it was relatively important to provide culturally sensitive treatment but that it was not as important to match clients in SUD centers with racially/ethnically similar counselors. Conclusion The topic of racial matching can be very complex and has shown variation amongst SUD centers; however, this study emphasizes the importance of providing culturally sensitive treatment and an appreciation of differences among members within each racial group.